ABILITY TO KNOW LETTERS THROUGH LETTER CARD GAME IN GROUP A IN PAUD DARUSALAM AR-RIZKI GEDONGTATAAN: Indonesia - Nurhadi Kusuma; Ruly Nadian Sari; Iis Maisaroh (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
ABSTRACT This study aims to improve the ability to recognize letters by using letter cards in early childhood group A in PAUD Darusalam Ar-Rizki. In the ability to recognize letters that are improved is to say letters, show letters, and connect letters. This research was conducted because of problems in recognizing letters in group A, where recognizing letters was still low. For this type of research is classroom action research conducted collaboratively between researchers and class teachers. For the object of this study, students of group A were 18 children. The method used for data collection is through observation and interviews. The results of this research are the ability to recognize letters of group A children in PAUD Darusalam Ar-Rizki can be improved using letter card media in the learning process of guessing letters on letter cards by bringing or holding letter cards directly and playing them according to the teacher's instructions. namely mentioning letters, indicating letters, and connecting letters. The results of this study indicate that there is an increase in the ability to recognize letters, namely in the pre-cycle by 22.6%, increasing in Cycle I to 54.8%, and in Cycle II an increase of 98.2%. from this explanation it can be understood increase in pre cycle to cycle I of 41.2%, and from cycle I to cycle II an increase of 53.7%. Keywords: games, letters, letter cards